Everyday violence - Van Loon, Julienne (Griffith University and ABC Books, 2006)
The Next Big Thing captures the reality of youth culture and contemporary cultural movements. It goes beyond the marketing hype about generation x and y and their baby boomer parents.The Next Big Thing is witty, insightful and provocative.